Cloud Computing Technologies: An Overview: Advantages and Empowering Features of Cloud Computing Technologies (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cloud computing is a model for empowering helpful, on-request network access to a mutual pool of configurable computing resources (e.g., networks, servers, storage, applications, and services) that can be quickly provisioned and released with negligible management exertion or service supplier communication (U.S. National Institute of Standards and Technology (NIST)). Cloud services are prevalent on the grounds that they can lessen the cost and many-sided quality of owning and working computers and networks. Since cloud clients don't need to put resources into information technology infrastructure, purchase hardware, or purchase software licenses, the advantages are low in advance costs, quick rate of profitability, fast arrangement, and customization, adaptable utilize, and arrangements that can make utilization of new developments.